2016
DOI: 10.21708/avb.2016.10.1.5390
|View full text |Cite
|
Sign up to set email alerts
|

SUSCEPTIBILIDADE ANTIMICROBIANA DE CEPAS DE Escherichia coli ISOLADAS DE AVES CONDENADAS POR COLIBACILOSE

Abstract: Este estudo tem por objetivo avaliar o perfil de susceptibilidade antimicrobiana de 130 cepas de Escherichia coli isoladas de aves condenadas por colibacilose pela Inspeção Federal no estado do Tocantins, procedentes dos estados de Distrito Federal (DF), Goiás (GO), São Paulo (SP) e Tocantins (TO), a realização do teste de sensibilidade aos antimicrobianos (TSA) seguiu a metodologia proposta por CLSI. Os resultados mostraram que 76% e 72% das cepas provenientes do estado do GO e TO, respectivamente, apresentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The presence of multidrug-resistant E. colichicken carcasses were recorded in other Brazilian regions (NEPOMUCENO et al, 2016;CARDOSO et al, 2015) and in other countries (ADORJÁN et al, 2020;AMIR et al, 2017;RAHMAN et al, 2020), supporting the need for surveillance of this bacterial species as a reservoir of antimicrobial resistance. The study data are similar to those of Vitas et al (2018), who found MDR phenotypes in E. coli isolated from chicken meat samples positive for extended spectrum, a major mechanism of antimicrobial resistance in gram-negative bacteria.…”
Section: Escherichia Coli Escherichia Colimentioning
confidence: 89%
“…The presence of multidrug-resistant E. colichicken carcasses were recorded in other Brazilian regions (NEPOMUCENO et al, 2016;CARDOSO et al, 2015) and in other countries (ADORJÁN et al, 2020;AMIR et al, 2017;RAHMAN et al, 2020), supporting the need for surveillance of this bacterial species as a reservoir of antimicrobial resistance. The study data are similar to those of Vitas et al (2018), who found MDR phenotypes in E. coli isolated from chicken meat samples positive for extended spectrum, a major mechanism of antimicrobial resistance in gram-negative bacteria.…”
Section: Escherichia Coli Escherichia Colimentioning
confidence: 89%